2021
DOI: 10.53854/liim-2903-11
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in COVID-19 fatality rate and risk of death: An analysis in 73 countries, 2020-2021

Abstract: There is a worrying lack of epidemiological data on the sex differential in COVID-19 fatality rates. We examined the Global Health 50/50 tracks of sex-disaggregated infection and mortality COVID-19 data from 73 countries through May 20, 2021. We compared the infection fatality rate (IFR) in men vs. women and risk of death from COVID-19 by country. Of all cases in 73 countries, 42,933,757 were in women and 40,187,894 in men; 1,274,663 men and 971,899 women died. The IFR was higher in males (3.17%) than in women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
1
11
1
Order By: Relevance
“…Males (vs. females) patients in our study sample were significantly older with higher proportion aged 60–69, and >70-years. Previously, it was found that mortality and fatality rates, which increase with age, are paramount in men over 50 years old ( 5 , 15 ). Most COVID-19 deaths occurred in patients over the age of 50, and the sex-dependent risk of poor outcomes increased with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Males (vs. females) patients in our study sample were significantly older with higher proportion aged 60–69, and >70-years. Previously, it was found that mortality and fatality rates, which increase with age, are paramount in men over 50 years old ( 5 , 15 ). Most COVID-19 deaths occurred in patients over the age of 50, and the sex-dependent risk of poor outcomes increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…As of May 20, 2021 and based on available sex-disaggregated data from the Global Health 50/50 investigators, the infection fatality rate (IFR) in males vs. females showed higher fatality rates in men, and this was also the case in other countries like Brazil, Yemen, Mexico, Scotland, and Guatemala. In total, men had significant higher odds of death from COVID-19 disease in 49 countries, when compared to women ( 15 ). As of May 2022, the latest data from the US showed a higher proportion of deceased male patients from COVID-19 vs. females (55% males and 45% females).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies on COVID-19 patients taken as a whole have shown that men are more susceptible than women to hospitalization and severe disease [2] , [3] . We have recently analyzed the report of the Italian National Institute of Health on SARS-CoV-2 positive cases considering age, sex and fatality index, reporting that men showed a fatality index significantly higher than that of women (OR 1.38, 95% CI 1.36–1.40, P < 0.0001), without any difference in infection rate [4] , [5] .…”
mentioning
confidence: 99%
“…With an increasing number of new cases and deaths, it has become clear that sex (understood as biological characteristics) plays an essential role in the epidemiology of COVID-19. According to global COVID-19 statistics, SARS-CoV-2 has affected a disproportionally higher number of males: although the morbidity rate was similar between sexes (slightly higher in men), the mortality rate was much higher among males [ 44 ].…”
Section: Discussionmentioning
confidence: 99%